Ferdinand De Saussure's Semiotic Analysis of The Poetry 'My Heart Is a Sheet of Leaves' By Sapardi Djoko Damono - Citra Puspita (Bulletin of Social Studies and Community Development, 2022)
Abstract: This study aims to analyze the poem entitled "Hatiku Selembar Daun" by Sapardi Djoko Damono, and to describe the results of the analysis of the poem. In this study the authors used a semiotic approach with the theory of Ferdinand De Saussure. After the poetry is analyzed semiotically using Ferdinand De Saussure's theory, it is hoped that it can provide knowledge about the meaning and linguistic signs that exist in the poem. The concept that will be analyzed in this article is a universal concept, namely a general concept that can be interpreted by almost everyone. Poetry is one of the prismatic literary works, meaning that poetry has a very broad openness of meaning. (Mustika and Isnaini, 2021).   Keywords: semiotics, literature, poetry.